2014
DOI: 10.1371/journal.pone.0094684
|View full text |Cite
|
Sign up to set email alerts
|

pix-1 Controls Early Elongation in Parallel with mel-11 and let-502 in Caenorhabditis elegans

Abstract: Cell shape changes are crucial for metazoan development. During Caenorhabditis elegans embryogenesis, epidermal cell shape changes transform ovoid embryos into vermiform larvae. This process is divided into two phases: early and late elongation. Early elongation involves the contraction of filamentous actin bundles by phosphorylated non-muscle myosin in a subset of epidermal (hypodermal) cells. The genes controlling early elongation are associated with two parallel pathways. The first one involves the rho-1/RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 22 publications
(87 reference statements)
5
40
0
Order By: Relevance
“…We observed that the head, body and tail diameter (at the levels of H1, V3 and V6, respectively) decreased at different rates over time (Figure 3c), as also observed by Martin and colleagues (Martin et al, 2014). The head diameter did not diminish between the 1.3F and 1.5F stages when the stress was nearly isotropic, but decreased significantly between the 1.5F and 1.7F stages as the stress anisotropy increased.…”
Section: Resultssupporting
confidence: 88%
“…We observed that the head, body and tail diameter (at the levels of H1, V3 and V6, respectively) decreased at different rates over time (Figure 3c), as also observed by Martin and colleagues (Martin et al, 2014). The head diameter did not diminish between the 1.3F and 1.5F stages when the stress was nearly isotropic, but decreased significantly between the 1.5F and 1.7F stages as the stress anisotropy increased.…”
Section: Resultssupporting
confidence: 88%
“…To correlate the stress anisotropy with the morphological changes of the embryo, we used markers 141 labelling cortical actin (an ABD) and junctions (HMR-1/E-cadherin). We observed that the head, body 142 and tail diameter (at the level of H1, V3 and V6, respectively) decreased at different rates over time 143 (figure 3c), as also observed by Martin and colleagues (Martin, 2014). The head diameter did not 144 diminish between the 1.3F and 1.5F stages when the stress was nearly isotropic, but decreased 145 significantly between the 1.5F and 1.7F stages as the stress anisotropy increased.…”
Section: Stress Anisotropy In Seam Cells Correlates With Embryonic Mosupporting
confidence: 81%
“…The role of the GTPases Rho/RHO-1 and Cdc42/CDC-42 in the ventral enclosure step of morphogenesis is only beginning to be described (Fotopoulos et al, 2013). In contrast, the role of RHO-1 in a later morphogenetic step, epidermal elongation, is exceedingly well studied (Diogon et al, 2007; Gally et al, 2009; Martin et al, 2014; Piekny et al, 2003; Piekny et al, 2000). Since hum-7 behaved genetically and molecularly like a candidate GAP for RHO-1 (and CDC-42), we investigated if hum-7 mutants have defects in Rho-dependent processes, like elongation.…”
Section: Resultsmentioning
confidence: 99%
“…During elongation the epidermis constricts circumferentially to squeeze the embryo into a tubular worm. Embryonic elongation also depends on regulators of Rho-1, and on Rho-1 targets including the Rho Kinase/LET-502 and non-muscle myosins (Chisholm and Hardin, 2005; Diogon et al, 2007; Fotopoulos et al, 2013; Gally et al, 2009; Martin et al, 2014; Piekny and Mains, 2003; Piekny et al, 2003; Quintin et al, 2008; Wissmann et al, 1997; Zhang et al, 2010). Elongation is driven by high levels of tension, mainly in the two rows of lateral seam cells.…”
Section: Introductionmentioning
confidence: 99%